Exploring the Impact of Built Environment Development on Activity Patterns of Public Open Space: The Case of Alun-alun Batu - Marhendra, Cantya Paramita (TATALOKA, 2025)
The redesign implemented at Alun-alun Batu in 2011 can be categorized as successful, not only for transforming it into a new social activity space but also as a driver of economic growth significantly impacting the lives of Batu City residents. This success has made Alun-alun Batu a benchmark project for similar projects. Over a decade, the built environment surrounding Alun-alun Batu has significantly transformed. The built environment's consistent development influences individual and community experiences, influenced by variations in spatial functions and designs within the area. This has also affected the quality of urban space, particularly in Alun-alun Batu, where shifts in social activities can alter community interactions and the utilization of its space. This research aims to provide an understanding of the impact of the built environment's development on the utilization of public open spaces at Alun-alun Batu. This study used data collected in 2013 and 2023 to analyze changes in activity patterns at Alun-alun Batu, with the 2013 data sourced from a prior study. The analysis focuses on the impact of built environment developments in the surrounding area and the effects of the pre- and post-COVID-19 periods on both the intangible and spatial aspects of space usage. Data collection in both years involved behavior mapping based on predetermined variables: person, milieu, and temporal aspects. Along with observations and interviews. The data were then qualitatively analyzed using a descriptive-comparative method. This study aims to provide valuable insights for future planning and design of Alun-alun Batu’s development.